Analysis of Energy Consumption in Commercial and Residential Buildings in New York City before and during the COVID-19 Pandemic - Branden M. Deiss (MDPI AG, 2021)
This study compares the energy burden of New York City office buildings versus personal residences before and during the stay-at-home period of the COVID-19 pandemic. The scope is comprised of employees that, prior to the stay-at-home order, underwent a daily commute to and from a representative midtown Manhattan office building. Energy consumed by these employees with respect to the office building they work in, their transportation there, and their personal residence was determined using publicly available data. Energy usage and cost per person per day were compared in both remote and in-person work settings. The results of this study demonstrated that remote working conditions consume 39.7% less energy and required less personal expense compared to in-person working conditions. Additionally, the results found that a building occupancy of 65% is where the energy burden shifts from residential to commercial sectors. This study can be a starting point of discussion for businesses regarding staffing of commercial buildings and energy efficiency. Future work on this topic would benefit from having a more robust data set compared to the publicly available data used in this study.